Accelerated Corneal Crosslinking for Treatment of Keratoconus in Children and Adolescents under 18 Years of Age - Xanthopoulou, Kassandra; Milioti, Georgia; Daas, Loay; Munteanu, Cristian; Seitz, Berthold; Flockerzi, Elias (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose To evaluate the efficacy of accelerated (9 mW/cm2, 10 min) epithelium-off (epi-off) corneal crosslinking (A-CXL) in keratoconus (KC) patients < 18 years of age.Patients and Methods Our retrospective study included 41 eyes (25 male and 5 female patients, mean age 15.3 ± 1.2 years) who underwent A-CXL (9 mW/cm2, 10 min) because of progressive KC or critical KC at first presentation or asymmetrical finding in the partner eye. Outcome measures were best-corrected visual acuity (BCVA) and tomography readings (Pentacam HR, Oculus, Wetzlar, Germany), evaluated 2 years, 1 year, 6 months preoperatively, prior to surgery (pre-CXL) and 6 weeks, 6 months, 1 year, 2 years, > 2 years postoperatively (post-CXL). The demarcation line was assessed by anterior segment optical coherence tomography (SS-1000 and CASIA 2, Tomey, Nagoya, Japan).Results Total deviation value increased statistically significantly 6 months pre-CXL to pre-CXL. Anterior steep, flat, and mean keratometry values showed a statistically significant increase 6 weeks post-CXL (p < 0.05), followed by a significant decrease until 2 years post-CXL for steep and mean keratometry. Kmax increased 6 weeks post-CXL without statistical significance and decreased significantly even > 2 years post-CXL (p < 0.0001). Posterior keratometry as well as anterior and posterior astigmatism did not show any significant changes post-CXL. Thinnest and apical pachymetry decreased significantly until 6 months post-CXL (p < 0.05) and remained stable > 2 years post-CXL (p > 0.05). BCVA decreased 6 weeks post-CXL but improved significantly > 2 years post-CXL (p = 0.003). The demarcation line reached an average depth of 52.1%.Conclusions Epi-off A-CXL stabilizes KC progression in patients < 18 years even > 2 years postoperatively and leads to a deep demarcation line. A “pseudoprogression” is observed up to the 6-week follow-up, which is not indicative of the long-term results.
Keywords: cornea; refractive surgery; physiological optics